2021
DOI: 10.1111/1745-9133.12558
|View full text |Cite
|
Sign up to set email alerts
|

Racial bias and DUI enforcement: Comparing conviction rates with frequency of behavior

Abstract: This study estimates disparities in driving under the influence (DUI) convictions relative to the frequency with which racial/ethnic groups engage in alcohol-impaired driving. We use had-been-drinking crashes and self-reported alcohol-impaired driving to approximate alcohol-impaired driving frequency for racial/ethnic groups in California from 2001 to 2016. DUI conviction and had-been-drinking crash data are from a sample of 72,368 California men aged 21-49 in 2001. Self-reported alcohol-impaired driving rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…33 Furthermore, the growing body of evidence demonstrating significant racial bias in legal convictions, including enforcement of driving under the influence, highlights the limitations of studying alcohol-associated legal issues. 34 …”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, the growing body of evidence demonstrating significant racial bias in legal convictions, including enforcement of driving under the influence, highlights the limitations of studying alcohol-associated legal issues. 34 …”
Section: Discussionmentioning
confidence: 99%
“…This policy may also increase race and gender inequality in impaired driving arrests (see Schwartz & Rookey, 2008;Kagawa et al, 2021). For example, Schwartz and Rookey (2008) indicated that the previous BAC limit change increased the proportion of women in DUI arrests by criminalizing the often less-serious (Lower BAC) drinking and driving behavior of women (Schwartz & Rookey, 2008).…”
Section: Lowering the Per-se Limit To 005mentioning
confidence: 99%
“…While prevalence rates of SUD tend to be lower among racial/ethnic minority groups (e.g., rates of lifetime alcohol use disorders [AUD] are 22.0% among Black persons, 22.9% among Latinx persons, and 32.6% among White persons; Grant, Goldstein et al, 2015), penalties related to substance use tend to be harsher for people of color. For example, the literature has shown a racial bias in driving under the influence (DUI) enforcement with Latino men having higher rates of DUI conviction than White men (Kagawa et al, 2021). This underscores the importance of continuing to center discussions of SUD around discrimination.…”
mentioning
confidence: 99%